SERVICE QUALITY OF GOODS AND SERVICES PROCUREMENT UNITS TOWARDS CUSTOMER’S SATISFACTION - Bayu Indra Setia; Atty Tri Juniarti; Rohmat Sarman; Erry S.R. Pangestu (Faculty of Economics and Business, University of Pasundan, 2020)
Subang District has become surprisingly attractive by the existence of Patimban Port. The presence of investor has given impacts to the number of studies and works requiring the performance of Procurement Service Units (trans. Unit Layanan Pengadaan – ULP) of goods and services that satisfy customers, namely the Regional Work Unit (trans. Satuan Kerja Perangkat Daerah – SKPD) and Partners. Method used are descriptive and verifiative by using path analysis. The service quality is measured with the dimensions of tangible, empathy, responsiveness, reliability, and assurance. The descriptive result showed that service quality and customers’ satisfaction were pretty good and dimension of responsiveness had smallest average score as well. Meanwhile, the verificative result showed that there were positive and significant effects, both simultaneously and partially, on the dimension of empathy, responsiveness, reliability, and assurance towards customers’ satisfaction.